New species of Chaetonerius Hendel (Diptera: Neriidae) from the Oriental Region - Sepúlveda, Tatiana A.; Marinoni, Luciane (Zootaxa, 2021)
The genus Chaetonerius Hendel has 25 valid species, predominantly distributed in the Afrotropical Region with only three species recorded for the Oriental Region. Herein, we describe a new species, Chaetonerius colavitei sp. n., from material collected in Thailand and Malaysia.